Description of Escherichia Coli Bacteria Content, Hygiene of the handler, and Sanitation of the selling place in Snack Food at State Primary School 4 Penganjuran Banyuwangi - Honi, Norika Rizqi (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Snack food is a type of food that is highly popular, especially among school-age children. Improper processing of snacks and lack of sanitary hygiene can make snacks vulnerable to biological, physical, and chemical contamination. This study aims to analyze the content of Escherichia coli bacteria, the hygiene of the handler, and the sanitation of the selling place in snack food at SDN 4 Penganjuran. This research is descriptive observational with a purposive sampling technique. There were nine samples of snacks involved in this study, including five samples of ice cubes, three samples of tomato sauce, and one sample of peanut sauce. Data on E. coli bacteria content was obtained from laboratory testing results using the MPN test. Meanwhile, data on the handlers’ hygiene and sanitation of the selling place were obtained from observations and interviews using a questionnaire. Data analysis was carried out univariately and continued with descriptive analysis in diagrams and tables. The results showed that 2 samples were positive for E. coli bacteria contamination. The handlers’ hygiene showed that 1 seller did not keep their hands and clothes clean, 3 sellers did not wear an apron or head cover, 7 sellers did not wash their hands before handling food, and 2 sellers served while scratching their body parts. Meanwhile, the sanitation of the selling place showed that 3 places were close to public trash bins, 2 sellers did not have hand washing water, and all of them did not provide closed trash bins at the selling location.